â€œIncidence of Antibiotic-Resistant Pseudomonas aeruginosa Isolated from Drinking Waterâ€ - Hirulkar, N.B. Hirulkar (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Pseudomonas aeruginosa has become increasingly recognized as an emerging opportunistic pathogen of clinical relevance. Several different epidemiological studies track its occurrence as a nosocomial pathogen and indicate that antibiotic resistance. Pseudomonas aeruginosa is a highly relevant opportunistic pathogen. One of the most worrisome characteristics of P. aeruginosa is its low antibiotic susceptibility. In present study drinking water samples were analyzed for its potability and presence of P. aeruginosa. Out of that 22 samples were found contaminated with P. aeruginosa. All 22 isolates showed maximum resistance to Levofloxin (50%) followed by Ciprofloxin (55%), and Gentamycin (51%) and Nitroflurantoin (51%), and Erythromycin (50%), and Co- trimaxazole (50%), and Oflaxacine (50%). The antibiotic like Tetracycline (46%), and Norfloxacin (46%), and Cephalexin (46%), and Metronidazole (46%), and Doxypal- Dr (46%), were moderately effective against the isolates and some antibiotic like Ampicillin (41%), Penicillin (41%) and Amixycellin (41%) were leess effective or minimum resistances against the isolates. The overall study concluded that the variation occurred in multiple antibiotic resistance patterns among various strains of Pseudomonas strains isolated from drinking water, indicated the emergence of antibiotic resistance, due to the indiscriminate use of antibiotics